2006
DOI: 10.1007/s11882-006-0038-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of allergic and nonallergic rhinitis on pediatric sinusitis

Abstract: There is a great deal of published evidence that there is a relationship between both allergic and nonallergic rhinitis and sinusitis in both pediatric and adult patients. The relationship between rhinitis and sinusitis may involve inflammation in one compartment leading to secondary inflammation in the other compartment, such as in the case of rhinitis leading to obstruction of the osteomeatal complex. The relationship may also involve individual manifestations of a shared process, such as allergic disease. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
(48 reference statements)
0
12
1
Order By: Relevance
“…Therefore, the contribution of allergy to the total inflammatory picture in CRS is debatable. In contrast to our results, other studies have shown that atopic patients suffer from more severe CRS . Negative effect of allergy on treatment outcome was also reported …”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the contribution of allergy to the total inflammatory picture in CRS is debatable. In contrast to our results, other studies have shown that atopic patients suffer from more severe CRS . Negative effect of allergy on treatment outcome was also reported …”
Section: Discussioncontrasting
confidence: 99%
“…PCRS can also occur and/or be aggravated by allergic rhinitis and adenoid disease. 4,5 The factors that may enhance the development of CRS include anatomical blockage, exposure to allergens and irritants, defects in mucociliary function, immunodeficiency, and bacterial, viral, and fungal infection. The frequent end result of these is local inflammation and swelling of the sinonasal mucosa leading to impairment of normal sinus drainage and secondary bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Allergic rhinitis may lead to nasal congestion and swelling of the membrane of the nasal mucosa which may, in turn, obstruct normal sinus drainage through osteomeatal complex [23]. There is also the possibility that inflammation in the nose and sinuses can be part of the allergic disease [23].…”
Section: Complicationsmentioning
confidence: 99%
“…There is also the possibility that inflammation in the nose and sinuses can be part of the allergic disease [23]. Patients with allergic rhinitis are therefore at increased risk for sinusitis [7].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation